Platelet membrane glycoprotein Ibα gene −5T/C Kozak sequence polymorphism as an independent risk factor for the occurrence of coronary thrombosis. Issue 1 (1st January 2002) - Douglas, H; Michaelides, K; Gorog, D A; Durante-Mangoni, E; Ahmed, N; Davies, G J; Tuddenham, E G D
Abstract : Objective: To explore the potential of the GPIbα gene variable number tandem repeat (VNTR) and −5T/C Kozak polymorphisms to act as independent risk factors for myocardial infarction. Methods: 256 patients aged 33–80 years (180 caucasian, 76 Indian Asian) were recruited at cardiac catheterisation for any diagnostic indication, and divided into two groups: group A, with confirmed previous myocardial infarction evident on ECG or ventriculogram (88 patients, 79 men, 9 women) and group B, with no evidence of myocardial infarction (168 patients, 101 men, 67 women). Results: There was no significant difference in race, age, hypertension, smoking status, or family history between the infarct and non-infarct groups, though there was a significant difference in sex (89.8% male in group A, 60.1% male in group B, p < 0.001). Genotype analysis showed a strong association between the GPIbα Kozak homozygous TT genotype and the occurrence of myocardial infarction (group A: TT 85.2%, TC 12.5%, CC 2.3%; group B: TT 67.3%, TC 32.7%, p = 0.001). No significant association was found between myocardial infarction and the GPIbα VNTR, although analysis of the CC VNTR genotype against all other GPIbα VNTR genotypes showed a marginal association with myocardial infarction (p = 0.059). There was no association between the Kozak sequence polymorphism (p = 0.797) or GPIbα VNTR (p = 0.714) and the degree of vessel disease. Conclusions: The homozygous TT Kozak genotype may be a significant factor in the outcome of coronary artery disease completed by myocardial infarction. Conversely, the Kozak C allele in the heterozygous state TC may confer some protection against myocardial infarction.